2021
DOI: 10.19087/jveteriner.2021.22.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Identification on Mackerel Tuna (Euthynnus Affinis) Brine Salting Traded in Tradisional Market of Semarapura, Klungkung, Bali

Abstract: Mackerel tuna (Euthynnus affinis) brine salting is a famous seafood product in Indonesia due to its good nutrition content. Bacterial contamination on this product may increase risk of foodborne diseases to happen, in addition to a decrease in quality and nutritionous value of the product. The main objective of this research was to identify bacteria contaminating the brine salting Mackerel tuna (Euthynnus affinis) sold in Tradisional Markets in Klungkung, Bali, Indonesia. Polymerase Chain Reaction (PCR) was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Based on the Chi-square test (Table 4) was obtained (p-value 0.2 > 0.05) which showed that there was no significant relationship between formalin and the level of bacterial contamination in cob pindang. It was found that there were 6 samples with total bacteria below the maximum allowable limit and 9 samples with total bacteria exceeding the maximum allowed limit (> 10 5 colonies/g) [14]. Formalin levels affect total bakeries in cob pindang fish, but in this study, a quantitative test was not carried out so the formalin levels in boiled cob fish were not known.…”
Section: Total Bacterialmentioning
confidence: 80%
See 1 more Smart Citation
“…Based on the Chi-square test (Table 4) was obtained (p-value 0.2 > 0.05) which showed that there was no significant relationship between formalin and the level of bacterial contamination in cob pindang. It was found that there were 6 samples with total bacteria below the maximum allowable limit and 9 samples with total bacteria exceeding the maximum allowed limit (> 10 5 colonies/g) [14]. Formalin levels affect total bakeries in cob pindang fish, but in this study, a quantitative test was not carried out so the formalin levels in boiled cob fish were not known.…”
Section: Total Bacterialmentioning
confidence: 80%
“…Bacillus cereus bacteria which are thermophilic (50°C), and Kurthia gibsonii are classified as psychotropic bacteria (4°C) [13]. The maximum limit for bacterial contamination in pindang fish is 1 x 10 5 colonies/gram [14].…”
Section: Microbes In Fishmentioning
confidence: 99%
“…14 On average, the Kusamba farmers yield the salts for a few kilos per day, and the process is sun-dependent, which means it can only be produced during the dry months. 15 A different study by Yogana et al (2016) emphasized points contributing to a significant plummet in Kusamba salt production. The pressures of the imported salt product, low income, and broker's grip dictated the market price.…”
Section: The Commodity's Profilementioning
confidence: 99%